2006
DOI: 10.1159/000091851
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response to Superantigen-Adsorbing Hemoperfusion in Toxin-Concentration-Controlled Septic Swine

Abstract: Background/Aims: Superantigens are suspected of being potent initiators of gram-positive sepsis, and new therapies for superantigen elimination are required. The effects of hemoadsorption with a superantigen-adsorbing device (SAAD) were evaluated in septic swine. Methods: Toxic shock syndrome toxin-1 (TSST-1) was infused, and blood concentration was maintained at the clinical level for 6 h. Endotoxin was then infused to induce lethal shock. All animals were hemoperfused with SAAD or a control column for 8 h an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Four kinds of cytokine adsorbers have thus far been developed: the CYT-860 [8,9,13,14] , Cytosorb [15,16] , CTR [17,18] , and MPCF-X [19] ; but there are very few clinical reports of these four adsorbers [18] . The CYT-860, which was evaluated in the present study, was originally developed as an exotoxin adsorber and found during the course of development to adsorb cytokines as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four kinds of cytokine adsorbers have thus far been developed: the CYT-860 [8,9,13,14] , Cytosorb [15,16] , CTR [17,18] , and MPCF-X [19] ; but there are very few clinical reports of these four adsorbers [18] . The CYT-860, which was evaluated in the present study, was originally developed as an exotoxin adsorber and found during the course of development to adsorb cytokines as well.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that this treatment inhibited increases in the blood bacterial count, plasma exotoxin level, and plasma IL-6 level [13] . Miwa et al [14] performed CYT-860-DHP treatment in a swine sepsis model prepared by the administration of toxic shock syndrome toxin-1 (TSST-1) and endotoxin, and reported significant improvement in the survival rate in the treatment group compared with the control group 24 h after the initiation of treatment (60 vs. 0%, p ! 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The question arises as to whether new sorbents can be developed to target the removal of specifi c pathogenic toxins and other infl ammatory mediators. Recent interest has centred on Gram-positive sepsis and the role of toxic shock syndrome toxin-1 (TSST-1), a superantigenic protein produced by Staphylococcus aureus which has been shown to produce multiple organ dysfunction in animal models similar to the human systemic infl ammatory response syndrome [10] . Preliminary animal experiments have shown improved animal survival, using specially developed haemoperfusion sorbents designed to remove Gram-positive peptidoglycans, TSST-1 and Gram-negative endotoxins in a model of endotoxin/TSST-1-induced multiple organ dysfunction.…”
mentioning
confidence: 99%
“…It has been demonstrated that devices capable of capturing toxins from plasma resulted in reduced mortality among septic animals compared to the untreated animals (Fenwick et al, 2003;Miwa et al, 2003Miwa et al, , 2006bTaniguchi et al, 2006). In these experiments a toxin-concentration-controlled animal model was used in which pigs were infused with TSST-1, and monitoring was performed for both the infusion period and a subsequent 1-h post-infusion period.…”
Section: Depletion Of Tsst-1 From Pig Plasma Using Fplc With An Anti-mentioning
confidence: 99%
“…Various adsorption devices have been developed that were shown to bind to endotoxins, cytokines and enterotoxins including TSST-1. Treatment of animals, with experimental sepsis and/or endotoxemia, using these devices resulted in reduced mortality compared with the animals which were left untreated (Fenwick et al, 2003;Miwa et al, 2003Miwa et al, , 2006bTaniguchi et al, 2006). A drawback of the adsorption devices used is that they bind a variety of small proteins which are not strictly defined and may also include beneficial molecules.…”
Section: Introductionmentioning
confidence: 99%